Identification of occult metastatic disease via lymphoscintigraphy‐guided neck dissection in N0 oral squamous cell carcinoma. Issue 7 (16th April 2022) - Earnest‐Noble, Lisa B.; Lipsky, Rachel S.; Kuhel, William I.; Kutler, David I.
Abstract: Background: The purpose of this study is to assess the efficacy of lymphoscintigraphy‐guided neck dissection (LSG‐ND) in the treatment of N0 oral squamous cell carcinoma. Methods: A retrospective cohort study of patients with N0 oral squamous cell carcinoma (SCC) who had either LSG‐ND or neck dissection (ND) at our institution between 2008 and 2020. Results: Eighty‐seven patients met criteria with N0 oral squamous cell carcinoma with no previous treatment or neck surgery (27 LSG‐ND, 60 ND). Sentinel lymph nodes were identified on the contralateral side in 14.8% of patients with unilateral tumors in the LSG‐ND group, with 22.2% of cases with unexpected lymphatic drainage outside ipsilateral levels I‐III. No recurrences to date have occurred in the LSG‐ND cohort, while 13.3% of patients with ND had regional recurrence ( p  = 0.04). Conclusions: LSG‐ND provides a greater ability to identify occult metastatic disease with a significant reduction in regional recurrence in N0 oral SCC.